Persepsi Nilai, Kepercayaan, Kepuasan Dan Minat Pasien Berkunjung Ulang Dalam Situasi Pandemi (Studi Pada Puskesmas Pangkah) - Irma Soulista Soulisa; Dwi Suryanto Hidayat (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The objectives of the study were: 1) analyzing the effect of perceived value on patient trust 2) analyzing the effect of perceived value on patient satisfaction 3) analyzing the effect of patient trust on patient interest in revisiting 4) analyzing the effect of patient satisfaction on patient interest in revisiting 5) analyzing the effect of perceived value on patient interest in revisiting 6) analyzing the effect of perceived value on patient interest in revisiting through patient trust 7) ​​analyzing the effect of perceived value on patient interest in revisiting through patient satisfaction. The population of this study were all patients who had visited the Pangkah Health Center as many as 1,077 patients. The sampling technique used two techniques, namely incidental sampling technique (accidental sample) and purposive sampling technique (criteria sample). The first stage is who are the patients who coincidentally come to the Pangkah Health Center. The second stage is selecting patients with the criteria for repeat visits (have visited before) at least two visits with a total of 100 patients. The results of the study are: 1) there is a positive and significant effect of perceived value on trust 2) there is a positive and significant influence on perceived value on satisfaction 3) there is no influence of trust on the patient's interest in revisiting 4) there is no effect of satisfaction on the patient's interest in revisiting 5) there is no effect of perceived value on patient interest in revisiting 6) there is no effect of perceived value on patient interest in revisiting through trust 7) ​​there is no effect of perceived value on patient interest in revisiting through satisfaction.